Double wounds: ecologies of trauma in Kivoshi Shigematsu’s “to next spring- Obon” and Osahon Ize- lyamu’s “more sea than tar” (2021)
Literature across cultures and nationalities has often taken a significant stance with ecoadvocacy. This study examines two short stories’ representation of cultural trauma exacerbated by the despoliation of the environment. Japanese Kivoshi Shigematsu’s “To Next Spring-Obon” and Nigerian Osahon Ize-Iyamu’s “More Sea Than Tar”, are chosen for their thematic convergence and topicality. Both stories are comparatively engaged through the trauma theory and ecocriticism, to investigate the stories’ recreation of personal as well as collective suffering tangled up with the larger tragedies occasioned by industrialization, modernity and most of all, environmental crises. The texts depict the environment and man as subjects that occupy oscillating positions between perpetrator and victim. The activities of man wound the environment and the environment responds by afflicting man, thereby causing traumatic disruptions that affect not just the present but the past and the future. In both texts, nature is a tower and a threat and man, a culprit cum casualty. In the aftermath of ecological catastrophes - the 3/11 in Shigematsu’s “To Next Spring- Obon” and a fictional tsunami in Ize-Iyamu’s “More Sea Than Tar”, man suffers spiritual and social degeneration, whose scars both stories serve to bear witness to.